PENGARUH E-SERQUAL TERHADAP COMMITMENT DAN SATISFACTION SEBAGAI VARIABEL INTERVENING “KASUS PENGGUNA E-BANKING DI KOTA PADANG” - Wirda Yaniariza; Syafrizal Syafrizal (Ekonis: Jurnal Ekonomi dan Bisnis, 2020)
In this digital edge, Indonesian Financial Service Authority (OJK) has encouraged bank industry to develop internet banking services. This service has changed the way customer interact with the bank from face to face interaction to online interaction. The development of this internet banking services have triggered marketing researcher to investigate how this service can influence customer satisfaction and commitment.  This study aims to examine the effect of internet banking service quality on customer satisfaction and commitment. A questionnaire survey has conducted to 130 bank customer’s in Padang. Research instruments of this study have been adapted from many previous studies. Structural Equation Model analysis technique has been used to analyze the data of this research. The result of this study found that the dimension of internet banking service quality such as easy to use, website design, privacy, responsiveness, efficiency and reliability have significant effect on customer satisfaction. Furthermore, it was found that customer satisfaction has significant effect on customer commitment.Keywords: Commitment, Stisfaction, E-Banking